De la Nouvelle Action française à la Nouvelle Action royaliste: Analyse du processus de mutation militante à partir d’une trajectoire organisationnelle nationaliste - Cucchetti, Humberto Horacio (2015)
The transformations that have occurred in the phenomenon of activism have merited several studies and explanations. The present work proposes to address these problems by considering a very specific case: the Nouvelle Action française, founded in 1971, which became the Nouvelle Action royaliste in 1978. The choice of this double scale, at the level of the selected empirical object as well as at the level of temporal delimitation, makes it possible to consider the events, issues and difficulties that lead a nationalist organization to change how it operates and its spaces of activism. In this way, the study of an activist compromise in a concrete case enables a political analysis which is not based on its ideological variables but on a whole set of practices, difficulties and conflicts present in the activist life of an organization. So there is an articulation between the generational maturing of the actors involved in a radical activism and a broader context where the political radicalization finds increasing limits. If the passage from a radical activism to association networks could constitute a simplistic formula that summarizes the process, the mutation of activism becomes a phenomenon that merits an investigation according to the peculiarities of every case analyzed.